Sirolimus use in patients with subglottic stenosis in the context of granulomatosis with polyangiitis (GPA), suspected GPA, and immunoglobulin G4-related disease. (2nd January 2021) - Poo, SX; Pepper, RJ; Onwordi, L; Ghufoor, K; Sandhu, G; Salama, AD
Abstract : Objective : Subglottic stenosis (SGS) is a severe, life-threatening disease found in immune-mediated diseases such as granulomatosis with polyangiitis (GPA) and in rare cases of immunoglobulin G4 (IgG4 )-related disease. It can result in persistent airway compromise due to the fibrotic response following inflammation. Standard management involves repeated endoscopic interventions to dilate the airway, and tracheostomy is occasionally required. In addition, immunosuppression remains a cornerstone of therapy aimed at controlling the underlying inflammatory disease; however, cumulative dosing leads to significant adverse effects. We present five cases of predominantly anti-neutrophil cytoplasmic antibody-negative GPA and a case of IgG4 -related disease with SGS, in whom we evaluated the long-term utility of sirolimus, which has beneficial anti-proliferative and fibrotic effects, in the management of their disease. Method : We conducted a retrospective review of a cohort of patients with SGS at a tertiary vasculitis unit. These patients were treated with sirolimus, in addition to conventional medical and endoscopic treatment. Clinical symptoms, frequency and time to endoscopic intervention pre- and post-treatment, additional rescue therapy, and any adverse effects were recorded and analysed. Results : Six patients were treated with sirolimus and followed for up to 9 years; two discontinued the drug owing to adverse effects, early on. In the remaining four patients, glucocorticoids were withdrawn, and the frequency of endoscopic intervention was reduced. One patient on sirolimus required rituximab therapy for disease flare. Conclusion : Sirolimus may be a therapeutic option for some patients with severe SGS, allowing steroid withdrawal and resulting in a positive adverse effect profile.